Effect of Different Solvents, Pore-Forming Agent and Solubility Parameter Differences on the Properties of PES Ultrafiltration Membrane - Seren Acarer (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2022)
In the production of polymeric membranes used in water treatment by the non-solvent-induced phase separation (NIPS) method, the materials used in the membrane casting solution and the interaction of these materials greatly affect the properties and performance of the obtained membranes. In this study, polyethersulfone (PES) membranes are produced by the NIPS method using two different solvents, dimethyl sulfoxide (DMSO) and N-methyl-2-pyrrolidone (NMP), and polyvinylpyrrolidone (PVP) as pore-forming agent. Chemical functional groups and morphologies of the produced membranes are investigated by Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM), respectively. The viscosity of the membrane casting solutions and the hydrophilicity, porosity, mean pore size, and mechanical properties of the membranes are characterized. The pure water flux (PWF) of the membranes is determined at 1 and 3 bar pressures. The Hansen solubility parameters (HSP) of the materials used in membrane production are calculated and the effect of the interactions of DMSO, NMP, and PVP with PES and/or non-solvent (water) on the membrane properties are investigated.